Green finance and urban carbon emission dual control: an empirical evidence from China - Zhang, Tian; Zhang, Yao; Zhang, Yumin (Frontiers in Environmental Science, 2025)
The Chinese government has proposed shifting the regulation of energy consumption and intensity towards a dual control system of total carbon emissions and carbon emission intensity gradually, aiming to promote the continued role of green finance in optimizing resource allocation. To reveal the impact and mechanism of green finance on urban carbon emissions and intensity in China, this paper constructs a general equilibrium model based on endogenous growth theory and employs a two-way fixed effects model for empirical testing. The study finds that: (1) The development of green finance significantly inhibits both the total carbon emissions and carbon emission intensity of Chinese cities. (2) The impact of green finance on urban carbon emissions and intensity exhibits significant regional heterogeneity. In the northeastern regions of China, southeastern regions of the Hu Line, non-resource-based cities, and areas with higher financial efficiency, green finance can significantly reduce both urban carbon emissions and carbon emission intensity. However, in central and western regions and resource-based cities, green finance only suppresses urban carbon emission intensity. (3) Green finance can reduce urban carbon emissions and intensity through two channels: economic scale expansion and technological advancement, while the channel of industrial structure optimization has not yet shown a significant effect. Through research, it can be found that balancing the differences in green finance and carbon emission functions across regions, while fully optimizing the use and allocation mechanisms of resource elements from aspects such as technological innovation, environmental protection, and energy conservation, can enhance the quality and efficiency of economic development. This is of significant importance for green finance in promoting the realization of dual carbon control.